A.01 Relieving the burden of myasthenia gravis: eculizumab reduces exacerbation, hospitalization and rescue therapy rates. (5th June 2019) - Siddiqi, Z; Howard, JF; Jacob, S; Guptill, JT; Meisel, A; Wiendl, H; Murai, H; Utsugisawa, K; Nowak, RJ; Fujita, KP; O'Brien, F; Patra, K; et al.
Abstract : Background: Patients with anti-acetylcholine receptor antibody-positive (AChR+) generalized myasthenia gravis (MG) unresponsive to conventional treatment experience greater disease burden than responsive patients. This is partly due to exacerbations, which may result in significant healthcare resource utilization. Eculizumab is well tolerated and gives clinically meaningful benefits in these patients. We evaluated the effect of long-term eculizumab treatment on exacerbations, hospitalizations and rescue therapy in the REGAIN study and its open-label extension.Methods: Exacerbations were defined as clinical worsening/deterioration, MG crises or rescue therapy usage; pre-study exacerbations/hospitalizations were defined from patient records. Event rates adjusted for patient-years were calculated for all patients in the pre-study year, patients receiving placebo during REGAIN, and patients receiving eculizumab during REGAIN and its open-label extension (median exposure, 27.5 months [range, 22 days–42.8 months]); rates were compared using a Poisson regression model.Results: Eculizumab treatment reduced exacerbations by 65% ( p =0.0057), hospitalizations by 71% ( p =0.0316) and rescue therapy use by 66% ( p =0.0072) versus placebo. Eculizumab treatment reduced exacerbations by 74% and hospitalizations by 83% (both p <0.0001) versus the pre-study year.Conclusions: Long-term eculizumab treatment reduces disease burden and healthcare resource utilization, demonstrating continuing improvements in clinical endpoints that lead to additional meaningful outcomes for patients with AChR+ generalized MG. (NCT01997229, NCT02301624).